A survey of core and support activities of communicable disease surveillance systems at operating-level CDCs in China - Li Liming; Lv Jun; Xiong Weiyi (BMC, 2010)
Abstract Background In recent years, problems like insufficient coordination, low efficiency, and heavy working load in national communicable disease surveillance systems in China have been pointed out by many researchers. To strengthen the national communicable disease surveillance systems becomes an immediate concern. Since the World Health Organization has recommended that a structured approach to strengthen national communicable disease surveillance must include an evaluation to existing systems which usually begins with a systematic description, we conducted the first survey for communicable disease surveillance systems in China, in order to understand the situation of core and support surveillance activities at province-level and county-level centers for disease control and prevention (CDCs). Methods A nationwide survey was conducted by mail between May and October 2006 to investigate the implementation of core and support activities of the Notifiable Disease Reporting System (NDRS) and disease-specific surveillance systems in all of the 31 province-level and selected 14 county-level CDCs in Mainland China The comments on the performance of communicable disease surveillance systems were also collected from the directors of CDCs in this survey. Results The core activities of NDRS such as confirmation, reporting and analysis and some support activities such as supervision and staff training were found sufficient in both province-level and county-level surveyed CDCs, but other support activities including information feedback, equipment and financial support need to be strengthened in most of the investigated CDCs. A total of 47 communicable diseases or syndromes were under surveillance at province level, and 20 diseases or syndromes at county level. The activities among different disease-specific surveillance systems varied widely. Acute flaccid paralysis (AFP), measles and tuberculosis (TB) surveillance systems got relatively high recognition both at province level and county level. Conclusions China has already established a national communicable disease surveillance framework that combines NDRS and disease-specific surveillance systems. The core and support activities of NDRS were found sufficient, while the implementation of those activities varied among different disease-specific surveillance systems.